Disaster Risk Governance in Coastal Community for A Better Normal: The Philippine Experience - Valenzuela, Victoria P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This study aims to: assess how local community stakeholders perceive disaster risk governance; determine the level of appreciation toward nature and environmental protection; train the local community stakeholders in climate change adaptation, disaster resilience and mitigation toward a cleaner, more productive, and better future through innovation and; identify the multi-stakeholders’ cooperation and their level of support to achieve sustainable lifestyles in coastal communities. Participatory action research was conducted in Malolos, Bulacan, Philippines with 155 respondents, while secondary data was reflected in this study. Survey instruments were patterned from Kaizer and Hartig (2011). The study views that nature and environmental protection as divergent manners turned out to be statistically associated. Gardening of various vegetables was introduced to women-residents to encourage them in engaging in nature and environment protection. The training on climate risk reduction, adaptation, and mitigation for barangay officials was conducted to protect coastal areas, preserving, and bringing back the beauty of nature was the contributory factor for multi-stakeholders’ cooperation for a better normal. The success of partnership among university, government, and barangay was manifested to community-based action research which can be seen as a paradigm of achieving sustainable lifestyles in responsive community engagement.